A Technique for Implementing Interactive Conversations - Manthey, Michael J. (DAIMI Report Series, 1976)
A general purpose parser for interactive command language construction is described. The method takes advantage of the characteristic of mini-computers that they are very often dedicated to a single user and thus during interaction can devote their computing capability entirely to the parsing (i.e. the parsing algorithm and be ’’wasteful’’ of computer time). Tables for the command language are generated by a different program which accepts an LL(1) grammar of the command language and produces output suitable for an assembler or compiler. The parsing algorithm is non-recursive and suitable for either character or graphic screens, but probably not for hard-copy devices.